2010
DOI: 10.1155/2011/156765
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic and Antioxidant Properties of Orthosiphon stamineus Benth (Cat′s Whiskers): Intervention in the Bcl‐2‐Mediated Apoptotic Pathway

Abstract: Antiapoptotic and antioxidant activities of aqueous-methanolic extract (CAME) of Orthosiphonstamineus Benth(OS), and its hexane (HF), chloroform (CF), n-butanol (NBF), ethyl acetate (EAF) and water (WF) fractions were investigated. Antioxidant properties were evaluated using the assays of Folin-Ciocalteu, aluminiumtrichloride, β-carotene bleaching and DPPH. The role of OS against hydrogen peroxide induced apoptosis on MDA-M231 epithelial cells was examined using MTT assay, phase contrast microscope, colorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
2
36
0
2
Order By: Relevance
“…Based on the situation of TPC and FRSA, methanolic extracts expressing good biological capacity. Besides that, in the extraction process, the polarity of solvents is very important to increase the solubility of antioxidant compounds [8]. Thus, it was significant to measure process to validate a good solvent in antioxidant compound extraction.…”
Section: Extraction By Differences Concentration Solventmentioning
confidence: 99%
“…Based on the situation of TPC and FRSA, methanolic extracts expressing good biological capacity. Besides that, in the extraction process, the polarity of solvents is very important to increase the solubility of antioxidant compounds [8]. Thus, it was significant to measure process to validate a good solvent in antioxidant compound extraction.…”
Section: Extraction By Differences Concentration Solventmentioning
confidence: 99%
“…The higher antioxidant properties in O. aristatus might be due to the properties of the plant that conferred with high amount of flavones, polyphenols, glycosides, bioactive active proteins, a volatile oil, and massive quantities of potassium [20]. Previous study of O. aristatus, indicated that total phenolic contents of the plant ranged from 139.81 to 386 gallic acid equivalents per gram of extract [21]. The content of phenolic and flavonoid compounds strongly link with the antioxidant activities of plant materials [22].…”
Section: Resultsmentioning
confidence: 99%
“…Although drying has been proven to maintain the beneficial properties of some plant samples, however, studies have shown that drying can also lead to the degradation of beneficial compounds within the leaf sample, such as phenolics (Abdelwahab et al, ; Chan et al, ; Potisate, Kerr, & Phoungchandang, ). This degradation could be due to two main factors, which are thermal degradation where the heat labile compounds are degraded at high temperature and oxidase enzyme activity such as polyphenol oxidase which utilizes phenolics as a substrate (Ayaz, Demir, Torun, Kolcuoglu, & Colak, ).…”
Section: Introductionmentioning
confidence: 99%